HUBUNGAN KOORDINASI MATA DAN KAKI DAN KECEPATAN REAKSI DENGAN KEMAMPUAN SEPAK SILA ATLET PPLP SEPAKTAKRAW RIAU - hayu, Tirka; Ramadi, Ramadi; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The Problem in this research is a soccer skill of athlete PPLP Sepaktakraw Riau were still lack of improvement, so when they got service from the opponent team, they tended to be slower response in lifting their legs which caused the ball rarely fit on part in their legs. This study aims to determine whether there is a relationship of eye and foot coordination and reaction of speed with the ability of football athletes of PPLP Sepaktakraw Riau. The type of this study is Correlation Research which has aims to find out level of relationship of different variables. The Technique of sampling were whole population (total sampling) athletes PPLP Sepak takraw Riau, which consisted of 15 athletes. The research conducted in Gor PPLP Riau Jl. Sutomo, Pekanbaru and in the Sports and Education Campus, Rumbai. The Instrument used in this research was eye and foot coordination, time meter reaction, and soccer skills. The Analysis done with the use of multiple correlation. Based on data analysis and discussion, it was proven with TCount of 0, 361 and Ttable 0.220. It means Tcount > Ttabel On level ɑ= 0.05. Then it could be concluded that there a significant relationship from eye and foot coordination and reaction speed with football skill athletes PPLP Sepaktakraw Riau .Keywords : Eye and foot coordination , Reaction of Speed, Football